Novel Effects of Leonardite-Based Applications on Sugar Beet - Della Lucia, Maria C.; Bertoldo, Giovanni; Broccanello, Chiara; Maretto, Laura; Ravi, Samathmika; Marinello, Francesco; Sartori, Luigi; Marsilio, Giovanni; Baglieri, Andrea; Romano, Alessandro; Colombo, Mauro; Magro, Francesco; et al. (Frontiers in Plant Science, 2021)
The present study aimed to explore the effects of foliar application of a leonardite-based product on sugar beet (Beta vulgaris L.) plants grown in the field. The approach concerned the evaluation of the community compositional structure of plant endophytic bacteria through a metabarcoding approach, the expression level of a gene panel related to hormonal metabolism and signaling, and the main sugar beet productivity traits. Results indicated that plants treated with leonardite (dosage of 2,000 ml ha-1, dilution 1:125, 4 mg C l-1) compared with untreated ones had a significant increase (p<0.05) in (i) the abundance of Oxalicibacterium spp., recognized to be endophyte bacterial genera with plant growth-promoting activity, (ii) the expression level of LAX2 gene, coding for auxin transport proteins, and (iii) and sugar yield. This study represents a step forward to advance our understanding of the changes induced by leonardite-based biostimulant in sugar beet.